ALINDROM AND SPEECH IN THE POETRY OF AZAM UKTAM AND MINHOJIDDIN MIRZO (Conferencea, 2021)
This article examines the palindrome and word game used in the poetry of the famous Uzbek poets Azam Uktam and Minhojiddin Mirzo.